2009
DOI: 10.1152/ajplung.90475.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neither fibrin nor plasminogen activator inhibitor-1 deficiency protects lung function in a mouse model of acute lung injury

Abstract: Allen GB, Cloutier ME, Larrabee YC, Tetenev K, Smiley ST, Bates JH. Neither fibrin nor plasminogen activator inhibitor-1 deficiency protects lung function in a mouse model of acute lung injury. Am J Physiol Lung Cell Mol Physiol 296: L277-L285, 2009. First published December 5, 2008 doi:10.1152/ajplung.90475.2008.-Fibrin impairs surfactant function in vitro, and inhibition of fibrinolysis by plasminogen activator inhibitor (PAI-1) is thought to promote fibrin accumulation in acute lung injury (ALI). This has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 65 publications
(90 reference statements)
2
17
0
Order By: Relevance
“…Slofstra et al (16) showed that inhalation of APC could attenuate LPS-induced lung inflammation and that APC-treated mice had a decrease in thrombin-anti-thrombin complexes in the bronchoalveolar lavage fluid. Furthermore, the few studies that have only modulated fibrin formation without affecting thrombin formation have shown results similar to the work of Allen and colleagues (2). Hyperoxia in PAI-1Ϫ/Ϫ mice as mentioned above had no effect on lung vascular leak even though fibrin deposition in the lung was reduced.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Slofstra et al (16) showed that inhalation of APC could attenuate LPS-induced lung inflammation and that APC-treated mice had a decrease in thrombin-anti-thrombin complexes in the bronchoalveolar lavage fluid. Furthermore, the few studies that have only modulated fibrin formation without affecting thrombin formation have shown results similar to the work of Allen and colleagues (2). Hyperoxia in PAI-1Ϫ/Ϫ mice as mentioned above had no effect on lung vascular leak even though fibrin deposition in the lung was reduced.…”
supporting
confidence: 66%
“…In their recent article, Allen et al (2) report findings from a mouse model of ALI that challenge our current understanding of the role of fibrin deposition in ALI. In this study, the authors use two different transgenic mouse models to reduce fibrin deposition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of Rho mobilized actin to form stress fibers and increased permeability, but activation of Rac prevented increases in endothelial permeability (54). Although coagulation factors significantly contribute to lung inflammation in many conditions, genetic deficiency in mice of either fibrin or PAI-1 did not protect against VILI (12).…”
Section: Free Radicals In Ventilator-induced Lung Injurymentioning
confidence: 99%
“…ALTHOUGH ANTICOAGULANT PROPERTIES of the vascular endothelial lining protect against clot formation, coagulation, and abnormalities of fibrinolysis are features of acute lung injury (ALI) (1,11,24,31). Thus ALI is associated with increases in procoagulant markers in the lung including fibrin deposition and increase of plasminogen activator inhibitor (PAI-1) in the bronchoalveolar lavage (BAL) (1,24,31).…”
mentioning
confidence: 99%